OPTIMASI VARIASI WAKTU PENGERINGAN DAN KECEPATAN TIUPAN UDARA PEMBAKARAN PADA PROSES PRODUKSI SILIKA DARI SEKAM PADI - Hendriwan Fahmi; Ronaldi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2013)
West sumatera is farmland so there are many rice miling industries.It produces hull of rice everyday and becomes disadvantages waste.Hull of rice contains silica has the shape of amorf terhidrat (Houston, 1972). Silica use as a material for producing ceremics. For producing dust from hull of rice which contains silica will be done by camouflage process and for testing silica composition in hull of rice dust is used XRF method. From the result of testing by using XRF method so be gotten the highest data from the hull of the rice silica in example with long drying variation as long as 2 hours with wind of blowing speed variation is 0.25 m/s with percentage Si02 is 98.12%.